Hubungan Tingkat Konsumsi Zat Gizi dan Tingkat Stres Psikologis dengan Kejadian Premenstrual Syndrome Pada Mahasiswi Indekos Usia 18–22 Tahun di Fakultas Farmasi Universitas Airlangga - Aurelia Dhea Fradista (Media Gizi Kesmas, 2023)
Background: Premenstrual Syndrome is a sequence of menstrual symptoms which occur before and during menstruation period. Factors that can influence the symptoms of premenstrual syndrome are nutritional consumption and psychological stress level. The variation in nutritional consumption and psychological stress level of heterogeneous co-ed caused differences in symptoms of premenstrual syndrome. Objectives: This study aims to analyze the correlation between nutritional consumption and psychological stress level with premenstrual syndrome to boarding house students in the Faculty of Pharmacy Universitas Airlangga. Methods: This study was an observational analitic study with a case-control design. The sample consisted of 28 co-ed with premenstrual syndrome and the other 28 co-ed who did not have premenstrual syndrome. The independent variable consists of the nutritional consumption and psychological stress level. The dependent variable is Premenstrual Syndrome. Data analysis used includes the Chi-Square test, Fisher Exact test, and Logistic Regression. Results: Results showed a significant correlation between energy consumption (p=0,027; OR=3,111), fat (p=0,026; OR=0,175), pyridoxine (p=0,035; OR=6,668), calcium (p=0,029; OR=0,134), magnesium (p=0,048; OR=9,155), and psychological stress levels (p=0,000; OR=0,041) with the incidence of premenstrual syndrome. In contrast, there was no correlation between the level of protein (p=0,589; OR=0,249) and carbohydrate consumption (p=0,252; OR=0,938) with the incidence of premenstrual syndrome. Conclusion: The conclusion of this study is the level of energy consumption, fat, vitamin B6, calcium, magnesium, and psychological stress levels can affect the symptoms caused by PMS. The advice for college students is that they should regulate their consumption by balanced nutrition guidelines.